Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1242/jeb.100511
|View full text |Cite
|
Sign up to set email alerts
|

Forward shift of feeding buzz components of dolphins and belugas during associative learning reveals a likely connection to reward expectation, pleasure and brain dopamine activation

Abstract: For many years, we heard sounds associated with reward from dolphins and belugas. We named these pulsed sounds victory squeals (VS), as they remind us of a child's squeal of delight. Here we put these sounds in context with natural and learned behavior. Like bats, echolocating cetaceans produce feeding buzzes as they approach and catch prey. Unlike bats, cetaceans continue their feeding buzzes after prey capture and the after portion is what we call the VS. Prior to training (or conditioning), the VS comes aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 52 publications
5
36
2
1
Order By: Relevance
“…These were short click trains of low (~2 ms for BJ and 2-5 ms for Kina), nearly constant or slightly increasing ICIs (Fig. 1) that may be analogous to the recently described victory squeals (VS) produced by trained belugas and bottlenose dolphins elsewhere (Ridgway et al, 2014). Because of their post-capture occurrence and their apparent communicative, rather than echolocation, function, the VS were disregarded in further ICI analyses (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These were short click trains of low (~2 ms for BJ and 2-5 ms for Kina), nearly constant or slightly increasing ICIs (Fig. 1) that may be analogous to the recently described victory squeals (VS) produced by trained belugas and bottlenose dolphins elsewhere (Ridgway et al, 2014). Because of their post-capture occurrence and their apparent communicative, rather than echolocation, function, the VS were disregarded in further ICI analyses (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was not until the development of sound recording tags that this interpretation could be substantiated. It is now clear that buzzes are associated with prey capture attempts in sperm whales (Miller et al, 2004), beaked whales , pilot whales (Aguilar Soto et al, 2008), porpoises (DeRuiter et al, 2009) and belugas (Ridgway et al, 2014).…”
Section: Short Communicationmentioning
confidence: 99%
“…Moreover, the fi sh tossed into the tank might have developed competition among the animals with an increase in production of burst pulses (Overstrom, 1983;Connor and Smolker, 1996;Herzing, 1996;Lammers et al, 2003;Nowacek, 2005). Moreover, Ridgway et al (2014) suggested that burst pulses produced during feeding sessions might be considered as food calls with emotional content. Nevertheless, more substantial experiments involving the diff erent aspects of food delivery should be carried out (food quantity and quality, hunger levels, and interaction with the keepers) (Dittus, 1984;Caine at al., 1995;Di Bitetti, 2005;Slocombe and Zuberbühler, 2006;Clay and Zuberbühler, 2009) to assess the presence of a referential content in the calls of dolphins ( Ralston and Herman, 1989 ;Herzing, 2000;Akiyama and Ohta, 2007;Therrien et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As they hunt for fish, the complex, asymmetrical, muscular nose makes brief, high-peak frequency click trains that are focused through the fatty melon-shaped forehead (Au, 1993;Jensen et al, 2009;Ridgway et al, 2014;Wisniewska et al, 2014). The clicks bounce off fish, returning echoes to the dolphin's ear (Au, 1993) where the cochlea converts the echoes into nerve impulses (McCormick et al, 1970(McCormick et al, , 1980.…”
Section: Introductionmentioning
confidence: 99%
“…The first two phases of fish capture, sonar clicking and the terminal buzz (TB), have received a good deal of attention in T. truncatus and other cetaceans (Au et al, 2013;Wisniewska et al, 2014). The victory squeal (VS) is a third phase (Ridgway et al, 2014). This third phase has not received as much attention with respect to fish capture.…”
Section: Introductionmentioning
confidence: 99%